PATTERNS AND DETERMINANTS OF BREAST FEEDING AMONG MOTHER INFANT PAIRS IN DERA GHAZI KHAN, PAKISTAN - Khan, Moazzam Ali; Qureshi, Zubia; Khan, Kauser Aftab; Gill, Fouzia Nadeem (Journal of Ayub Medical College Abbottabad, 2016)
Background: Proper breastfeeding practices are effective ways for reducing childhood morbidity and mortality. The objective of the present study was to determine the patterns and explore the determinants associated with breast feeding practices among the nursing women in Dera Ghazi Khan. Methods: A cross sectional study was conducted on randomly selected lactating mother infant pairs in Dera Ghazi Khan. Structured questionnaire was used for data collection. Analysis was done by using SPSS, chi square test was applied to see the association between breast feeding practices and its determinants such as knowledge of breast feeding practices. Results: Majority 372 (93%) of mothers mentioned that they had ever breastfed the youngest child. About 292 (73%) mothers gave colostrum to the child, and 48 (12%) exclusively breastfed. Weaning babies before four month of age was practiced by 84 (21%) of the mothers, 120 (55%) mothers started weaning at 4-6months of child age, while 72 (18%) started to give additional food after baby turned six months old. Out of total 276 (69%) mothers reported that they had knowledge regarding breast feeding. Significant association was found between knowledge of breastfeeding and initiation and Exclusive Breast Feeding (EBF) practices (p-values <0.05). Income, family type, mode of delivery and assistance for child were significantly associated with initiation of breastfeeding within one hour after birth (p-value <0.001). Conclusion: Breast feeding practices in the studied area were not up to the mark. There is a strong need to improve the breastfeeding practices by Behavior Change Communication. Keywords: Breast feeding; Early initiation; Exclusive Breast Feeding (EBF); Colostrum; Supplementary feeding; Infants